ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN KEMUDAHAN AKSES TERHADAP KEPUASAN PENGUNJUNG DI PLANETARIUM DAN OBSERVATORIUM UIN WALISONGO SEMARANG - sopi, sopi; Mina, Muhammad Saefuddin (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
Tourism is one of the important sectors as the mainstay of the country's economic resources, especially when the tourist attractions are visited by foreign tourists. The purpose of this study was to determine whether the quality of service, price, and ease of access to visitor satisfaction at the Planetarium and Observatory UIN Walisongo. This study took a sample of 100 visitors. The data analysis technique used to solve the problems in this study is to use regression analysis. This analysis is used to determine and obtain an overview of the effect of service quality (X1), price (X2), and ease of access (X3) on visitor satisfaction (Y) at the Planetarium and Observatory of UIN Walisongo. Data processing in this study using the SPSS computer program. The test results obtained first, the service quality variable obtained a t-count value of 3.687 with a significance value of 0.001 smaller than 0.05 and the regression coefficient has a positive value of 0.393. So this study succeeded in proving the first hypothesis which says that “there is a positive effect of service quality on visitor satisfaction at the UIN Walisongo Planetarium and Observatory”. Second, the price variable obtained a t-count value of 2.106 with a significance value of 0.038 smaller than 0.05 and the regression coefficient has a positive value of 0.212. So this study succeeded in proving the second hypothesis which says that “there is a positive effect of price on visitor satisfaction at the Planetarium and Observatory of UIN Walisongo”. Third, the ease of access variable obtained a t-count value of 2.268 with a significance value of 0.026 smaller than 0.05 and the regression coefficient has a positive value of 0.216. So this study succeeded in proving the third hypothesis which says that “there is a positive effect of promotion on visitor satisfaction at the Planetarium and Observatory of UIN Walisongo”. The conclusion in this study is that service quality (X1), price (X2), ease of access (X3) have a positive effect on visitor satisfaction (Y) planetarium and Observatory UIN Walisongo. Suggestions in this study are to provide services to customers should be in accordance with established service standards. can pay attention to prices well.